Hubungan Penggunaan Obat Antipsikotik dengan Kepatuhan Minum Obat pada Pasien Skizofrenia : A Cross-Sectional Study - Nurul Amna; Ellyza Fazlylawati; Khaira Rizki; Urip Pratama (Pusat Riset dan Inovasi Nasional, 2025)
Medication non-compliance in schizophrenia patients has the potential to have significant negative impacts on the patient's clinical condition, the continuation of therapy, and the surrounding social environment. Low medication adherence can lead to symptom relapse, increased hospitalization rates, and a decreased quality of life. Therefore, efforts to minimize these impacts need to be directed at improving medication adherence, one of which is through identifying factors that influence adherence and selecting appropriate antipsychotic medications. This study aims to determine the relationship between antipsychotic medication use and medication adherence in schizophrenia patients. The research design used was a quantitative cross-sectional study approach. The study sample size was 195 respondents, obtained using a systematic random sampling method. The research instruments included an antipsychotic medication use sheet and the Morisky Medication Adherence Scale (MMAS). Data analysis was performed using the Chi-Square test to determine the significance of the relationship. The results showed that patients given typical antipsychotic medications had a higher adherence percentage (49.4%) compared to patients receiving atypical antipsychotic medications (27%) or a combination (23.6%). These findings confirm a significant relationship between the type of antipsychotic medication and patient adherence (χ² = 7.307; p = 0.026). The study's conclusions emphasize that the choice of antipsychotic, particularly typical antipsychotics, can be an important factor in improving medication adherence in patients with schizophrenia. Therefore, healthcare professionals are expected to carefully consider the type of medication prescribed, while still taking into account the patient's clinical condition, side effects, and individual needs, so that adherence and therapeutic success can be optimized.